Families’ experiences of the Low Arousal Approach: a qualitative study - McDonnell, Andrew Austin; Page, Andrea; Bews-Pugh, Stephanie; Morgalla, Karolina Anna; Kaur-Johal, Tarendeep; Maher, Mary (Frontiers in Psychology, 2024)
Background: Parents and carers supporting a family member presenting with behaviours of concern experience heightened stress. The Low Arousal Approach is a crisis management strategy which recognises that stress, or physiological arousal, can be expressed through behaviours of concern. This approach aims to equip parents and carers to manage behaviours in a person-centred and non-confrontational way. There is a paucity of published research exploring the experiences of families applying this approach.Methods: Seventeen parents who had received training in the Low Arousal Approach were interviewed to gain their perspectives on supporting their family members using this approach.Results: Thematic Analysis revealed themes relating to parental stress, which was related to external pressures, isolation, family stress, and challenges in their caring role. They described encountering negative narratives relating to self-criticism and negative judgments FAMILIES EXPERIENCES OF THE LOW AROUSAL APPROACH 2 from others. Training in the Low Arousal Approach was related to being empowered through access to evidence, increased confidence, and increased ability to advocate for their family member's needs. Low Arousal was described as a "lifestyle" that enabled increased coping for the family unit as a whole.Discussion/Conclusions: Findings indicate that it is vitally important to recognise the views of parents and carers, and these are equally as important as the views of professionals.We must understand parents' and carers' needs in order to provide adequate support.